Predictors of ectopic pregnancy in nulliparous women: A case-control stud - Ahmed Ragab; Yasser Mesbah; Ibrahim El-Bahlol; Muhammed Fawzy; Mohamed Alkhatim Alsammani (Middle East Fertility Society Journal, 2016)
Objective: To investigate risk factors of ectopic pregnancy (EP) in nulliparous women and the main lines of treatment offered. Methods: A case-control study was conducted from January 2013 to December 2014 at Mansoura University Hospitals, Egypt. A total of 36 cases of EP in nulliparous women were included. Each case was matched to 2 healthy subsequent pregnant nulliparous women. Data were gathered by using a questionnaire. Odds ratios were adjusted for the confounding factors using multiple logistic regression models. The main outcome measures were predictors of EP. Results: There were no significant differences in age and gravidity between cases and controls (p > 0.05). The main predictors of EP were history of pelvic inflammatory diseases (PID) (OR = 10.14, 95% CI = 3.382–30.435, p < 0.001), infertility treatment (OR = 8.7, 95% CI = 1.4–55.3, p = 0.021), and past pelvi-abdominal surgery (OR = 4.1, 95% CI = 1.3–13.3, p = 0.017). The primary treatment involved laparoscopic salpingectomy in 86.1% (n = 31 cases), and 8.3% (n = 3 cases) were offered methotrexate treatment meanwhile 2 cases (5.6%) were treated by laparotomy. Conclusion: The study concluded that common risk factors for EP in nulliparous women were PID followed by infertility treatment and past pelvi-abdominal surgery. The main line of treatment was laparoscopic salpingectomy followed by methotrexate and laparotomy.